Effects of Antiarrhythmic Drugs on hERG Gating in Human-Induced Pluripotent Stem Cell-Derived Cardiomyocytes From a Patient With Short QT Syndrome Type 1 - Huang, Mengying; Liao, Zhenxing; Li, Xin; Yang, Zhen; Fan, Xuehui; Li, Yingrui; Zhao, Zhihan; Lang, Siegfried; Cyganek, Lukas; Zhou, Xiaobo; Akin, Ibrahim; Borggrefe, Martin; et al. (Frontiers in Pharmacology, 2021)
Aims: The short QT syndrome type 1 (SQT1) is linked to hERG channel mutations (e.g., N588K). Drug effects on hERG channel gating kinetics in SQT1-cells have not been investigated. Methods: This study used hiPSC-CMs of a healthy donor and a SQT1-patient carrying the N588K mutation and patch clamp to examine the drug effects on hERG channel gating kinetics. Results: Ajmaline, amiodarone, ivabradine, flecainide, quinidine, mexiletine and ranolazine inhibited the hERG channel current (IKr) less strongly in hiPSC-CMs from the SQTS1-patient (SQT1-hiPSC-CMs) comparing with cells from the healthy donor (donor-hiPSC-CMs). Quinidine and mexiletine reduced, but ajmaline, amiodarone, ivabradine and ranolazine increased the time to peak of IKr similarly in SQT1-hiPSC-CMs and donor-hiPSC-CMs. Although regarding the shift of activation and inactivation curves, tested drugs showed differential effects in donor- and SQT1-hiPSC-CMs, quinidine, ajmaline, ivabradine and mexiletine but not amiodarone, flecainide and ranolazine reduced the window current in SQT1-hiPSC-CMs. Quinidine, ajmaline, ivabradine and mexiletine differentially changed the time constant of recovery from inactivation, but all of them increased the time constant of deactivation in SQT1-hiPSC-CMs. Conclusion: The window current-reducing and deactivation-slowing effects may be important for the antiarrhythmic effect of ajmaline, ivabradine, quinidine and mexiletine in SQT1-cells. This information may be helpful for selecting drugs for treating SQT1-patients with hERG channel mutation.